Helminth Parasites of Zoonotic Importance in Dog Faeces of North-Western Region of Pakistan: An Environmental Threat to Public Health - Wali KHAN; Ata ULLAH; Shakeel AHMAD; Yasir INAM (Tehran University of Medical Sciences, 2020)
No Abstract